Prevalence and pattern of Diabetic Foot Ulcers among adults with Diabetes mellitus in a secondary health care facility in Lagos, Nigeria - Odusan O; Amoran EO; Salami O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2017)
Introduction: The prevalence of diabetes mellitus with the attendant complications is increasing worldwide, contributing significantly to the health and socioeconomic burden of individuals, family and health care system. Objective: To determine the prevalence and pattern of diabetic foot ulcers recorded among patients with diabetes at the General Hospital Marina, Lagos. Methods: A descriptive cross-sectional study involving all the consecutively recruited attendees at the Out-patient Clinic was conducted between February and July 2014 using a semi-structured questionnaire. Results: Six hundred and twenty adults were invited to the study out of which 8 declined, giving a response rate of 98.7%. The mean age of the participants, mostly females (78.9%), was 61.1±11.0 years. The subjects had lived with diabetes mellitus for more than 3years (76.3%) and had a mean blood glucose level of 136.4±59.7mg/dl. Over two-thirds of them (79.6%) were receiving oral anti-diabetic drugs with a history of poor drug compliance in more than three-quarters (485; 79.2%). The prevalence of Diabetic Foot Ulcer was 17.3%; these presented as swelling (37; 34.9%), blisters (33; 31.1%), trauma (25; 23.6%) and burns (11; 10.4%). The prevalence was associated with female gender and age above 60 years (p = 0.0001 and p = 0.005 respectively). None of the other socio-demographic characteristics had significant association with the presence of diabetic foot ulcers. Conclusion: This study revealed a high prevalence of diabetic foot ulcers, especially among the elderly females. Patient education on diabetes should include foot care as this may reduce its prevalence and burden.